Oracle database administration for Microsoft SQL server DBAs - Malcher, Michelle (Emeryville, Calif. : McGraw-Hill, 2011)
"Use your SQL Server experience to set up and maintain a high-performance Oracle Database environment. Written by a DBA with expertise in both platforms, Oracle Database Administration for Microsoft SQL Server DBAs illustrates each technique with clear explanations, examples, and comparison tables. Get full details on Oracle Database internals, creation assistants, management techniques, and query tools. High availability, disaster recovery, and security procedures are also extensively covered in this comprehensive Oracle Press guide"
Includes index
Keywords: Database management; SQL/ORACLE (Computer program language)